Slum Conditions in Haryana and Pro-poor Housing Initiatives in Faridabad, India (International Journal of Built Environment and Sustainability, 2017)
Rapid urbanization forces urban poor to live in slums and squatter settlement. In neo-liberal development approach, participatory planning and collaborative actions are becoming popular in slum upgrading programmes. This paper discusses the slum scenario in state of Haryana along with detailed pro-poor housing attempts in industrial city of Haryana i.e. Faridabad. The paper reviews the three projects that aimed to improve the living conditions and lives of urban poor communities in Faridabad. The study examines in detail BSUP projects at Dabua Colony and Bapu Nagar taken up under India’s first urban renewal mission i.e. JNNURM within the context of community participation. Results reveal that contrary to the state’s rhetoric of inclusive governance, the urban poor are completely excluded from settlement planning, leading to a lack of understanding of their needs by the state. BSUP housing scheme has failed to mobilize slum dwellers. Drawing on the experience of these projects, the paper seeks to answer the question: why the stated objectives were not achieved and makes recommendation that community led initiatives and slum mapping should be at the core of slum improvement strategy so that qualitatively superior areas can be planned for the unprivileged.